Lesotho - Education Sector Development Project - Mastri, Lawrence (2012)
The objectives of the Education Sector Development Project (ESDP) addresses critical needs in the areas of basic education, such as expanding access through the construction, and furnishing of new classrooms. The project aimed to revise curricula, develop instructional materials, and strengthen the system of assessment. In addition to recruiting more teachers, training for teachers at both pre-and-in service was planned to upgrade the standards of teaching. To address the needs of students enrolled in Technical and Vocational Education programs, the project proposed to introduce standardized craft curricula, strengthen skills certification and testing, and improve policy and management capacity within the sub sector. The project planned to support the National University of Lesotho in its efforts to introduce quality enhancement and cost containment measures. Finally, the objectives included improving sectoral management by reorganizing the Ministry of Education (MOE), promoting decentralization, and school level management.